The Contradiction of Between Judge’s Decision and Legal Provisions Regarding The Position of Heirs in Proof of Land Rights - Adont, Sulistiani; Syarifuddin, La; Al Hidayah, Rahmawati (Jurnal Mulawarman Law Review, 2018)
As the economic development of Indonesian society increases, so will the need for legal certainty in the field of land for the right holder of a plot of land. the fundamental issue in verifying the right to the land is any person claiming to have a right, or appointing an event to affirm his right or to deny any right of another person, shall prove the existence of that right or prove the event, the heirs' a case study of the Samarinda District Court Judgment Number 138 / Pdt.G / 2014 / PN.Smr.This research uses normative research method. The primary legal material of this research is the legislation that is compiled into a conceptual form based on existing legislation. Which then conducted legal analysis of the problems in this study.The result of the research is the position of the heirs in verification of the right to land must have at least two evidences, that can prove that the heirs are valid first through the certificate of inheritance. To strengthen the verification of the heirs to the land rights, the heirs must prove by means of evidence as set forth in Article 24 paragraph (1) of Government Regulation Number 24 of 1997 concerning Registration. The second result of the research is the letter of appointment by the Government/Local Government is a valid evidence based on existing legislation, and it becomes the base of the right which is the basis of the land ownership, the analysis of the judge's decision namely the judge decision of Samarinda District Court No. 138 / Pdt.G / 2014 / PN.Smr is incorrect and does not provide legal certainty, it is caused by no reference what is contained in Article 24 paragraph (1) and Article 32 paragraph (2) Government Regulation Number 24 of 1997 on Land Registration.